THE WILDERNESS ONLINE: HOW INTERACTIVITY IS CHANGING MUSIC VIDEOS ON THE INTERNET - Forelle, Michelle (AoIR Selected Papers of Internet Research, 2015)
This paper explores interactive music videos as a new area for academic inquiry. It provides a history of music videos leading up to the ascendance of interactive music videos, and then explores a series of projects to illustrate the range of approaches the genre covers. Finally, the paper produces a brief analysis of the genre, meant more to stimulate future, more focused analyses than to represent an exhaustive review of the field.